Increased consumption of calcium from fat-free milk, energy-restricted diet and educational activities improves metabolic control in overweight type 2 diabetic patients - Costa, Jorge de Assis; Gomes, Júnia Maria Geraldo; Ribeiro, Priscila Vaz de Melo; Alfenas, Rita de Cássia Gonçalves (British journal of nutrition, 2020)
We assessed the effects of increased Ca consumption from fat-free milk in an energy-restricted diet and educational activities in the metabolic control of overweight type 2 diabetes mellitus (T2DM) patients. Fourteen subjects with T2DM (BMI 29·4 ( sd 4·5) kg/m 2 , low habitual Ca consumption (<600 mg/d)) were included in this randomised, crossover clinical trial. Subjects were randomly allocated to one of the two interventions: drink containing 700 mg of Ca (DAIR) or drink containing 0 mg of Ca (CONT) for ninety consecutive days each. Energy-restricted diets (–500 kcal/d; –2092 kJ/d), containing 800 mg of Ca from dietary sources/d, were prescribed for both groups. Questionnaires were applied at baseline and at the end of the study to assess the subjects’ knowledge on the disease and on self-care, biochemical variables and physical activity. Blood pressure, food intake, body composition and anthropometry were assessed at baseline, days 45 and 90. There was a higher reduction of body fat %, waist circumference, hip circumference, neck circumference, waist:hip ratio, sagittal abdominal diameter, diastolic/systolic blood pressure and an increase in fat-free mass % in DAIR than in CONT. Uric acid, fasting glucose, Hb1Ac, parathyroid hormone and alanine aminotransferase concentrations reduced and vitamin D concentration increased after 90 d in DAIR compared with CONT. The consumption of energy-restricted diet containing 1200 mg Ca/d seems to favour metabolic control in subjects with T2DM. The educational activities increased the knowledge on the disease care.